Knowledge and attitudes of nursing students regarding the sexuality of older adults: a quasi-experimental study - Ana Carolina Macri Gaspar Vendramini; Rosemeiry Capriata de Souza Azevedo; Priscila Aguiar Mendes; Janderson Diego Pimenta da Silva; Annelita Almeida Oliveira Reiners; Amanda Cristina de Souza Andrade (Revista Brasileira de Enfermagem)
ABSTRACT Objectives: to compare the knowledge and attitudes of nursing students regarding sexual behavior and sexually transmitted infections (STIs) in older adults before and after an educational intervention. Methods: this quasi-experimental study involved a convenience sample of 45 nursing students from a public university, conducted in three stages: pre-intervention, intervention, and post-intervention. A questionnaire was used to assess sociodemographic characteristics, academic training, and knowledge and attitudes on the topic. The intervention was an educational web conference. Paired t-test and Wilcoxon test were used for data analysis. Results: there was a statistically significant difference in the knowledge and attitude scores of nursing students before and after the educational intervention (p < 0.001). A significant increase was observed in the knowledge score (from 9.3 to 12.2) and attitude score (from 108 to 117.2) in the post-intervention phase. Conclusions: the knowledge of nursing students regarding the sexuality of older adults increased after the educational intervention, and their attitudes on the subject became more positive.